Feasibility and pilot study of an intervention to support active lifestyles in youth with type 1 diabetes: The ActivPals study. Issue 3 (24th November 2017) - Mitchell, Fiona; Wilkie, Louise; Robertson, Kenneth; Reilly, John J; Kirk, Alison
Abstract : Background: Evidence suggests youth with type 1 diabetes (T1D) have lower levels of physical activity (PA) than the general population. The ActivPals intervention aimed to support youth with T1D to lead an active lifestyle. Methods: Twenty youth aged 7 to 16 years with T1D were recruited to a pilot randomized controlled trial. PA and quality of life (QoL) were measured using Actigraph GT3X+ monitor and Pediatric QoL scales at baseline and 1‐month follow‐up. A two‐way, mixed ANOVA showed indicative effects of the intervention. Qualitative interviews were carried out with 16 participants to explore perceptions of the intervention. Results: An increase in moderate to vigorous PA was reported in intervention and control groups from baseline to follow‐up ( F (1, 14) = 5.83; P = .03), with no significance between group differences. Participants in both groups reported significantly less overall diabetes "problems" ( F (1, 16) = 7.93; P = .012) and significantly less lifestyle "problems" ( F (1, 16) = 7.39; P = .015) at follow‐up. However, both groups also reported significant increases in "problems" with the day‐to‐day diabetes routine ( F (1, 16) = 6.48; P = .022) at follow‐up. Parents reported significant increased worry about their child's diabetes at follow‐up, in both groups ( F (1, 14) = 5.83; P = .046). There was no significant increase in reported hypoglycemic occurrences despite increased PA. The qualitative data highlight that goal setting, self‐monitoring, and social support were effective motivators for increasing PA. Conclusions: A larger trial with longer follow‐up should be conducted to explore the effect of the intervention on PA in youth with T1D.